The Impact of Education and Motivation on the Capacity and Development of Generation Z - Sasmita, Vina; Rizky, M. Chaerul; Ramadiah, Aisyah; Juanda, Amar Firdaus; Putri, Artika (LifeSciFi, 2025)
Education and motivation are pivotal in shaping the development of individuals and communities, particularly for Generation Z, who face unique socio-economic challenges in rural settings. This study aims to analyze the influence of education and motivation on the skills, mindset, and future prospects of Generation Z in Kuala Air Hitam Village, Langkat Regency, North Sumatra. A quantitative approach was employed, with data collected through questionnaires distributed to 44 respondents aged 13 to 28 years. The data were analyzed using descriptive statistics, validity tests, reliability tests, normality tests, heteroscedasticity tests, multicollinearity tests, multiple linear regression, F tests, and T-tests. The findings confirm that education and motivation together significantly affect potential of Generation Z, explaining 60.8% of the variation in their outcomes, with motivation having a stronger influence (t = 4.313, significance = 0.000) than education (t = 3.496, significance = 0.001). Both variables independently contribute to enhancing skills and prospects. The study concludes that integrating educational improvements with motivational programs is essential to unlock the potential of Generation Z, enabling them to overcome rural challenges and contribute to sustainable community development. Collaborative efforts among stakeholders are recommended to support these initiatives.